In vivo effect of celecoxib and tenoxicam on oxidant/anti-oxidant status of patients with knee osteoarthritis - Ozgocmen, S; Ardicoglu, O; Erdogan, H; Fadillioglu, E; Gudul, H (Assoc Clinical Scientists, 2005)
The aim of this study was to compare the in vivo effects on free radical metabolism of 2 nonsteroidal anti-inflammatory drugs (NSAIDs): tenoxicam, an oxicam preferentially cyclooxygenase-1 (COX1) inhibitor, and celecoxib, a sulfonamide selective COX-2 inhibitor. The serum levels of oxidative stress-related enzymes (ie, xanthine oxidase (XO), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px)), of a lipid peroxidation marker (malondialdehyde (MDA)), and of nitric oxide (NO) in patients with knee osteoarthritis were studied at baseline and after a 4-wk course of treatment with celecoxib (n = 11) and tenoxicam (n = 12). Celecoxib-treated patients had significant decrease in nitrite levels (p = 0.043), whereas SOD, XO, GSH-Px enzyme activities, and MDA levels did not change significantly compared to baseline. Tenoxicam-treated patients had significant decrease in nitrite levels (p = 0.036) and XO activity (p = 0.01), but their SOD, GSH-Px enzyme activities, and MDA levels were unchanged from baseline. There was significant correlation between the patients' (n = 23) Western Ontario and McMaster Universities (WOMAC) LK3.0 Osteoarthritis Index, WOMAC-pain scores, and MDA levels (r = 0.50, p = 0.014) and the patients' WOMAC-stiffness scores and XO enzyme activity (r = 0.46, p = 0.027) at baseline. Significant improvement was found in pain-VAS, patients' global assessment, and WOMAC pain, stiffness, and physical function scores in celecoxib and tenoxicam- treated groups. In summary, our study revealed that tenoxicam may have antioxidant effects, and that celecoxib and tenoxicam may reduce nitrite levels, indicating an alteration of NO pathways.
Keywords: osteoarthritis; celecoxib; tenoxicam; oxidative stress; free radicals; nitric oxide